2016
DOI: 10.1021/acs.energyfuels.6b02359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 Dissolution on the Rheology of a Heavy Oil/Water Emulsion

Abstract: KEYWORDSRheology, heavy crude oil, emulsion, carbon dioxide, viscosity, non-Newtonian fluid ABSTRACT During the later stages of flow from an oil well, water inevitably appears in the produced fluids.When crude oil and water are energetically mixed by constrictions in the production tubing, emulsions can form. Heavy crudes may also contain surface-active agents that can stabilise the emulsion, resulting in persistent flow problems. If carbon dioxide is injected into such a reservoir (e.g. for CO2 EOR), then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is found from Figure a–c that x CO 2 is quickly increased with the pressure up to a certain pressure threshold, above which x CO 2 is increased gradually and finally reaches its maximum. The gaseous CO 2 is much more easily dissolved into the oil phase than the liquid CO 2 . On the other hand, y HCs is slightly decreased at a lower pressure, which is followed by an obvious increase starting from the threshold pressure, at which a strong HCs extraction occurs because the liquid CO 2 has a stronger extraction ability than the gaseous CO 2 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is found from Figure a–c that x CO 2 is quickly increased with the pressure up to a certain pressure threshold, above which x CO 2 is increased gradually and finally reaches its maximum. The gaseous CO 2 is much more easily dissolved into the oil phase than the liquid CO 2 . On the other hand, y HCs is slightly decreased at a lower pressure, which is followed by an obvious increase starting from the threshold pressure, at which a strong HCs extraction occurs because the liquid CO 2 has a stronger extraction ability than the gaseous CO 2 .…”
Section: Resultsmentioning
confidence: 98%
“…The gaseous CO 2 is much more easily dissolved into the oil phase than the liquid CO 2 . 53 On the other hand, y HCs is slightly decreased at a lower pressure, which is followed by an obvious increase starting from the threshold pressure, at which a strong HCs extraction occurs because the liquid CO 2 has a stronger extraction ability than the gaseous CO 2 . At an even higher pressure, y HCs increases much more gradually because most light to intermediate HCs in the oil phase have already been extracted.…”
Section: Energy and Fuelsmentioning
confidence: 98%
“…This is also contrary to the conclusion obtained by Johnsen and Rønningsen, which demonstrated that the phase inversion point shifts to a higher water fraction after the dissolution of light hydrocarbons, from about 80% to about 90%. As for the study of the CO 2 -dissolved emulsion, Hu et al recently designed a circulation system that could be employed to test the rheology of the CO 2 -saturated crude oil emulsion . However, the measurement process was still accomplished with a rheometer, so it is only applicable to uniform and stable emulsions, but not suitable for the unstable oil–water–gas mixed fluid.…”
Section: Introductionmentioning
confidence: 99%
“…As for the study of the CO 2 -dissolved emulsion, Hu et al recently designed a circulation system that could be employed to test the rheology of the CO 2 -saturated crude oil emulsion. 18 However, the measurement process was still accomplished with a rheometer, so it is only applicable to uniform and stable emulsions, but not suitable for the unstable oil−water−gas mixed fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The blue line represents CO 2 flow, and the black line represents the crude oil mixtures. Reprinted with permission from Hu et al 14 . Copyright 2016 American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%